DevOps and business : aligning business and IT goals for operational efficiency - Fayer, Leon (O'Reilly Media, 2019)
DevOps is much more than a set of practices to eliminate silos between development and operations groups. If your company's DevOps transformation is to succeed, you need to blur the lines between business and technology domains. This report helps engineering leaders understand what drives the business and provides best practices for aligning technology with business goals to increase efficiency and improve the bottom line. Author Leon Fayer, vice president of software development at Teaching Strategies, provides methods and techniques to help your organization improve cross-departmental processes, cooperation, and visibility. Getting IT and business groups to adopt DevOps principles will go a long way toward accomplishing that goal. This report shows you how. Use practical strategies to teach stakeholders how DevOps can provide value for the business Quantify the ROI value of DevOps implementation and culture changes Determine the best ways to position technology groups to support business outcomes Improve communication efficiency to identify mistakes and optimize service delivery Understand the importance of continuous insight into business performance Build empathy and trust by encouraging people to support common goals and solve problems together.